The south China sea disputes : formula for a paradigm shift? - Raul (Pete) Pedrozo (2014)
China does not have valid territorial claims to the South China Sea islands. To suggest that Beijing should be permitted to claim an exclusive economic zone from these islands is counterproductive and will put China one step closer to achieving de facto control of the South China Sea. ASEAN nations can stand by and allow China to incrementally solidify its maritime claims in the South China Sea through threats and coercion or they can stand up to Chinese brinkmanship before it’s too late.